I. DEVELOPMENTAL METHODOLOGY AS A CENTRAL SUBDISCIPLINE OF DEVELOPMENTAL SCIENCE. Issue 2 (June 2017) - Card, Noel A.
Abstract : This first chapter introduces the main goals of the monograph and previews the remaining chapters. The goals of this monograph are to provide summaries of our current understanding of advanced developmental methodologies, provide information that can advance our understanding of human development, identify shortcomings in our understanding of developmental methodology, and serve as a flagpost for organizing developmental methodology as a subdiscipline within the broader field of developmental science. The remaining chapters in this monograph address issues in design (sampling and big data), longitudinal data analysis, and issues of replication and research accumulation. The final chapter describes the history of developmental methodology, considers how the previous chapters in this monograph fit within this subdiscipline, and offers recommendations for further advancement.